Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

(a+b)² = a²+2ab+b² prove that.​

Sagot :

Answer:

see explanation

Step-by-step explanation:

(a + b)²

= (a + b)(a + b)

Each term in the second factor is multiplied by each term in the first factor, that is

a(a + b) + b(a + b) ← distribute parenthesis

= a² + ab + ab + b² ← collect like terms

= a² + 2ab + b²

Answer:

(a+b) is squared which means (a+b)(a+b)

Lets prove it

= (a+b)(a+b)

= a(a+b) + b(a+b) (Here a will mutiply by (a+b) and b will mutiply with (a+b)

= a²+ab + ab + b²

= a²+ 2ab + b²

Hence proved (a+b)² = a²+ 2ab + b²

please click thanks and mark brainliest if you like :)